Altitude-Dependent and Host Variety in Fruit Fly Populations: A Study on Bactrocera spp. in East Java - Hamdoen, Fadel Muhammad; Tarno, Hagus; Syamsulhadi, Mochammad; Gandaseca, Seca (Research Journal of Life Science, 2024)
Oriental fruit fly (Bactrocera spp.) are one of the most invasive pests, known for their severe impact on causing damage to wide variety of comodities. In Indonesia, as an agricultural country, possesses vast agricultural areas, in which Bactrocera fruit flies pose a persistent threat to production, particularly in regions known for horticulture. This study aims to identify key environmental drivers influencing their distribution and abundance. A cross-sectional study was conducted across thirteen locations located in four regencies and cities within East Java, Indonesia. Fruit fly samples were collected using a purposive random sampling method, with the quantity of samples adjusted to the fruit availability at the research site. The results showed that B. albistrigata, B. carambolae, and B. dorsalis exhibit strong ecological overlap, sharing similar host plants and environmental preferences, which facilitate their coexistence. Furthermore, the research provides a foundation for predicting potential shifts in population distribution in response to climate change, enabling proactive measures to safeguard vulnerable agricultural systems.